Effects of Allicin on Late Sodium Current Caused by ΔKPQ-SCN5A Mutation in HEK293 Cells - Chen, Yating; Huang, Yun; Bai, Jing; Liu, Chuanbin; Ma, Shanshan; Li, Jiaxin; Lu, Xu; Fu, Zihao; Fang, Lihua; Li, Yang; Zhang, Jiancheng (Frontiers in Physiology, 2021)
Aim The aim was to study the effect of Allitridum (Allicin) on the heterologous expression of the late sodium current on the ΔKPQ-SCN5A mutations in HEK293 cells, with a view to screening new drugs for the treatment of long QT syndrome type 3 (LQT3). Methods and Results The ΔKPQ-SCN5A plasmid was transiently transferred into HEK293 cells by liposome technology and administered by extracellular perfusion, and the sodium current was recorded by whole-cell patch-clamp technology. Application of Allicin 30 μM reduced the late sodium current (INa,L) of the Nav1.5 channel current encoded by ΔKPQ-SCN5A from 1.92 ± 0.12 to 0.65 ± 0.03 pA/pF (P < 0.01, n = 15), which resulted in the decrease of INa,L/INa,P (from 0.94% ± 0.04% to 0.32% ± 0.02%). Furthermore, treatment with Allicin could move the steady-state inactivation of the channel to a more negative direction, resulting in an increase in channel inactivation at the same voltage, which reduced the increase in the window current and further increased the inactivation of the channel intermediate state. However, it had no effect on channel steady-state activation (SSA), inactivation mechanics, and recovery dynamics after inactivation. What’s more, the Nav1.5 channel protein levels of membrane in the ΔKPQ-SCN5A mutation were enhanced from 0.49% ± 0.04% to 0.76% ± 0.02% with the effect of 30 mM Allicin, close to 0.89% ± 0.02% of the WT. Conclusion Allicin reduced the late sodium current of ΔKPQ-SCN5A, whose mechanism may be related to the increase of channel steady-state inactivation (SSI) and intermediate-state inactivation (ISI) by the drug, thus reducing the window current.